1983
DOI: 10.1002/ijc.2910320509
|View full text |Cite
|
Sign up to set email alerts
|

Decreased natural killer activity in patients with liver cirrhosis

Abstract: Natural killer (NK) activity of peripheral blood mononuclear cells from patients with non-alcoholic liver cirrhosis (LC) (30 cases), patients with other, non-malignant diseases (41 cases), and healthy subjects (36 cases) were investigated using 51Cr-labelled CCRF-CEM and K562 target cells. NK activity in patients with LC was lower than that in healthy subjects and that in patients with other, non-malignant diseases. The differences were statistically significant by Student's t-test and the Wilcoxon rank test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…These include changes in intestinal permeability, altered gut motility, gastrointestinal bleeding, bacterial overgrowth and changes in hepatic clearance, all of which may favour bacterial translocation and the development of endotoxemia [2,[36][37][38][39]. Other changes include dysfunction of the reticuloendothelial system, 90% of which is located within the liver [40,41], a reduction in the phagocytic capacity of monocytes and impaired function of macrophage Fc receptors [42,43], acquired deficiency of complement C3 due to reduced hepatic synthesis [44], deficient neutrophil recruitment and impaired phagocytic activity [45], reduced opsonic activity of ascitic fluid [46], decreased natural killer cell activity [47] and a marked reduction in leukocyte chemotaxis [48]. Finally, the cirrhotic patient is often subjected to invasive procedures that increase risk of nosocomial infection.…”
Section: Discussionmentioning
confidence: 96%
“…These include changes in intestinal permeability, altered gut motility, gastrointestinal bleeding, bacterial overgrowth and changes in hepatic clearance, all of which may favour bacterial translocation and the development of endotoxemia [2,[36][37][38][39]. Other changes include dysfunction of the reticuloendothelial system, 90% of which is located within the liver [40,41], a reduction in the phagocytic capacity of monocytes and impaired function of macrophage Fc receptors [42,43], acquired deficiency of complement C3 due to reduced hepatic synthesis [44], deficient neutrophil recruitment and impaired phagocytic activity [45], reduced opsonic activity of ascitic fluid [46], decreased natural killer cell activity [47] and a marked reduction in leukocyte chemotaxis [48]. Finally, the cirrhotic patient is often subjected to invasive procedures that increase risk of nosocomial infection.…”
Section: Discussionmentioning
confidence: 96%
“…A reduction in peripheral blood NK activity in patients with liver cirrhosis (LC) has been reported (12,13,21,28). Hata et al investigated hepatic NK activity using transplanted liver and reported a reduction in hepatic NK activity in advanced liver disease.…”
mentioning
confidence: 99%
“…Both liver cirrhosis and obstructive jaundice are known to result in some kind of immune defect: liver cirrhosis results in polyclonal hypergammaglobulinaemia with enhanced concentrations of IgG, IgM, IgA (Feizi, 1968;Wilson et al, 1969;Iturriaga et al, 1977;Husby et al, 1977) and IgE (van Epps et al, 1976), but cellular immunity is defective; peripheral blood T cells (Bereny et al, 1974;Thomas et al, 1976), delayed-type hypersensitivity (MacSween & Thomas, 1973;Berenyi et al, 1974;Thomas, 1977), lymphocyte proliferation (MacSween & Thomas, 1973;Berenyi et al, 1974) and natural killer cell function (Nakamura (? ;Charpentiere/fl/., 1984) are all diminished in liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%